Clinical manual of pediatric consultation-liaison psychiatry - Shaw, Richard J., 1958 July 1-; DeMaso, David R. (David Ray), 1949- (American Psychiatric Association Publishing, 2020)
"Completely updated to reflect advances in research and treatment options, Clinical Manual of Pediatric Consultation-Liaison Psychiatry provides practitioners with concise and pragmatic ways of organizing the key issues that arise in psychiatric consultation with physically ill children and their families. Covering all of the common clinical psychiatric consultation questions that arise in the pediatric hospital this book is designed for both novice trainees approaching their first pediatric consultation-liaison psychiatry rotations and advanced and experienced practitioners seeking information on psychopharmacological management of physically ill children. Chapters 1-4 provide an overview of pediatric consultation-liaison psychiatry, including assessment principles and legal and forensic issues. Chapters 5-14 are devoted to specific psychiatric symptoms and disorders in physically ill children and adolescents. Chapters 15-18 address issues related to treatment and intervention. New to the second edition are discussions of catatonia, serotonin syndrome, neuroleptic malignant syndrome, autoimmune encephalitis, and pediatric acute-onset neuropsychiatric syndrome (PANS), as well as an overview of fabricated or induced illness symptoms"--